Analyzing cellulolytic bacteria diversity in mangrove ecosystem soil using 16 svedberg ribosomal ribonucleic acid gene - I. Dewiyanti; D. Darmawi; Z.A. Muchlisin; T.Z. Helmi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Soil is an essential abiotic component serving as a habitat for numerous organisms, including cellulolytic bacteria commonly found in mangrove ecosystems. This bacteria could produce active enzymes needed to improve environmental quality by accelerating the organic matter decomposition. The unique mangrove environment may contain new types of cellulolytic bacteria with new characteristics. Despite several mangrove areas being explored as sources of cellulolytic bacteria, there is currently unexplored data on its diversity in Aceh Province, Indonesia. Accordingly, it is necessary to analyze the molecular biological approach, namely the 16 svedberg ribosomal ribonucleic acid gene, to identify the diversity of cellulolytic bacteria and analyze the phylogenetic relationships between them.METHODS: Bacteria isolates were collected from mangrove soil at six research locations with three replications. A purposive sampling method was applied to determine the research location. Isolates from soil samples were streaked and purified in carboxymethyl cellulose as selective media for cellulolytic bacteria. Molecular identification adopted 16 svedberg ribosomal ribonucleic acid gene sequencing, and the sequencing data were matched with GenBank data. Phylogenetic analysis and genetic distance between species were evaluated using molecular evolutionary genetics analysis.FINDINGS: Thirteen isolates were sequenced, and nine species of cellulolytic bacteria dominated by the Bacillus genus were identified. These species exhibited an identity value of 97.77-100 percent when compared to data from GenBank, and B. velezensis was found to have a close relationship with B. amyloliquefaciens at a value of 0.002 percent. Interestingly, the non-rehabilitated mangrove areas had more bacterial species than the rehabilitated ones. Two Bacillus genus had different nucleotide bases, proving they were distinct species.CONCLUSION: Nine cellulolytic bacteria species were identified; the two closely interspecies genetic distance related were B. velezensis and B. amyloliquefaciens, whereas the farthest were Bacillus sp1. and Bacillus sp2. Small genetic distances of interspecies indicate a close relationship between species. In comparing the two sampling sites, the non-rehabilitated mangrove contains higher bacterial cellulolytic species than the rehabilitated and Bacillus-dominated site. The findings provide valuable insights into the diversity of cellulolytic bacteria in mangrove ecosystems. The abundance of bacterial species could serve as sources of cellulase enzymes with different characteristics, essential in an environmental aquatic management.